2018
DOI: 10.1128/aac.02266-17
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Drug Tolerance of Mycobacterium tuberculosis in Caseum

Abstract: Tuberculosis (TB) recently became the leading infectious cause of death in adults, while attempts to shorten therapy have largely failed. Dormancy, persistence, and drug tolerance are among the factors driving the long therapy duration. Assays to measure in situ drug susceptibility of Mycobacterium tuberculosis bacteria in pulmonary lesions are needed if we are to discover new fast-acting regimens and address the global TB threat. Here we take a first step toward this goal and describe an ex vivo assay develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
209
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(221 citation statements)
references
References 50 publications
12
209
0
Order By: Relevance
“…These physiological changes (either stochastically- or environmentally-induced) result in antibiotic tolerance, in which MTB is genetically susceptible to antibiotics but exists in a physiological state rendering it refractory to drug killing. These persistent states are a major reason why long courses of antibiotic therapy are required to treat human tuberculosis (TB) (2); standard chemotherapy of TB requires 6 months of treatment and 5% are not cured even then (3, 4). There is an urgent need for new strategies that shorten the duration of treatment and target drug tolerant MTB.…”
Section: Introductionmentioning
confidence: 99%
“…These physiological changes (either stochastically- or environmentally-induced) result in antibiotic tolerance, in which MTB is genetically susceptible to antibiotics but exists in a physiological state rendering it refractory to drug killing. These persistent states are a major reason why long courses of antibiotic therapy are required to treat human tuberculosis (TB) (2); standard chemotherapy of TB requires 6 months of treatment and 5% are not cured even then (3, 4). There is an urgent need for new strategies that shorten the duration of treatment and target drug tolerant MTB.…”
Section: Introductionmentioning
confidence: 99%
“…The authors linked the diminished activity of clofazimine with the development of hypoxic, caseous necrotic lesions containing extracellular bacteria, suggesting that clofazimine was less active within these lesions. This hypothesis was further supported by studies demonstrating that clofazimine diffuses relatively poorly into caseous necrotic lesions in humans TB (27), does not have bactericidal activity in ex vivo caseum from M. tuberculosis -infected rabbits (41), and the long-standing observation that clofazimine accumulates in macrophages (26, 27, 42, 43). Rifapentine has been shown to diffuse into necrotic caseous lesions less rapidly than rifampin in a rabbit model of cavitary TB (28), a finding that correlates with clinical data indicating that replacing rifampin with rifapentine added proportionally less activity in patients with cavitary versus non-cavitary TB disease (44).…”
Section: Discussionmentioning
confidence: 81%
“…For intracellular bacilli, the drug must also overcome the barrier of the host cell membrane and, in many cases, an encapsulating vesicular membrane, as well as potential sequestration by the different organelles and intracellular bodies within different cell types (11,12). The occupation of discrete host loci (13–15) presents an additional confounder (Figure 1), in that individual bacteria from a clonal infecting population are characterized by different physiological states, and this can impact drug susceptibility (11,16,17) and the ability of the drug to penetrate the complex mycobacterial cell wall (18), as well as subverting the active compound’s activity against a metabolic target that might be essential only under specific conditions (19,20). As if that weren’t already sufficiently complex, host-mediated (21,22) and/or mycobacterium-mediated (23,24) biotransformation might further complicate the passage of drug from ingestion by the patient to its intrabacillary target (7).…”
Section: Introductionmentioning
confidence: 99%
“…Using a combination of New Zealand White rabbits, imaging mass spectrometry, three first-line anti-TB drugs (INH, RIF, and PZA), and the fluoroquinolone MXF, the group demonstrated that drug plasma concentration was indeed a poor proxy for drug concentration in TB lesions (8). The lack of data on how this might translate into humans combined with the absence of cellular protein binding data were acknowledged as weaknesses by the authors; nevertheless, this work prompted a growing appreciation of the need to include permeation studies in their drug development pipeline (16,129,130). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation